2020
DOI: 10.3390/pathogens9070515
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus A in Brazil: Molecular Epidemiology and Surveillance during 2018–2019

Abstract: Rotavirus A (RVA) vaccines succeeded in lowering the burden of acute gastroenteritis (AGE) worldwide, especially preventing severe disease and mortality. In 2019, Brazil completed 13 years of RVA vaccine implementation (Rotarix™) within the National Immunization Program (NIP), and as reported elsewhere, the use of Rotarix™ in the country has reduced childhood mortality and morbidity due to AGE. Even though both marketed vaccines are widely distributed, the surveillance of RVA causing AGE and the monitoring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 63 publications
5
23
1
Order By: Relevance
“…An increase in genotype diversity was also observed in the vaccine era, with the equine-like G3P [8] variant detected in Ireland [27]. The equine-like G3P [8] variant was also reported by Gutierrez et al, where it was the dominant genotype observed in Brazil in 2018 and 2019 [28]. This study also reported a significantly higher positivity rate among children aged >24-60 months compared to other age groups [28].…”
supporting
confidence: 82%
“…An increase in genotype diversity was also observed in the vaccine era, with the equine-like G3P [8] variant detected in Ireland [27]. The equine-like G3P [8] variant was also reported by Gutierrez et al, where it was the dominant genotype observed in Brazil in 2018 and 2019 [28]. This study also reported a significantly higher positivity rate among children aged >24-60 months compared to other age groups [28].…”
supporting
confidence: 82%
“…Till now, 36 genotypes of G and 51 P have been reported worldwide (9). The epidemiological studies indicate that at least six human RVA genotypes G1P [8], G2P [4], G3P [8], G4P [8], G9P [8], and G12P [8] are globally prevalent in human infections (10).…”
Section: Introductionmentioning
confidence: 99%
“…The second-round semi-nested multiplex PCR was performed using G-type-specific primers: G1-G4, G9, and G12; and P-type-specific primers: P [4], P [6], and P [8] [27−29]. For untypable samples, multiplexed one-step genotyping method with new G-and P-target specific primers was performed to identify G1−G4, G9, and G12; and P [4], P [6], P [8], P [9], and P[10] [30]. For those samples that still remained untyped were subjected to nucleotide sequencing.…”
Section: Genotype Identification Of Rvamentioning
confidence: 99%